Diagnóstico e certificação de sustentabilidade do Campus I da Universidade Federal da Paraíba por métricas globais - Figueirêdo, Marina Lima (2024)
Higher Education Institutions (HEIs) face an increasing educational responsibility regarding sustainability. HEIs consume a significant amount of resources, such as water and energy, and generate large quantities of solid waste. In this context, it is essential to adopt sustainability policies and initiatives. Participation in global university sustainability rankings reflects the commitment of HEIs to promoting sustainable development. Thus, the general objective of this work is to evaluate different global sustainability metrics and apply the most widely recognized international methods to Campus I of the Federal University of Paraíba. The specific objectives are to conduct a sustainability diagnosis of Campus I of UFPB; respond to the 2023 UI GreenMetric World University Rankings (UIGM-WUR) global questionnaire for sustainability certification; evaluate UFPB's participation in the 2023 Times Higher Education Impact Ranking (THE-IR) in Sustainable Development Goals (SDGs) compatible with UIGM-WUR categories; quantify UFPB's sustainability practices according to the score obtained in UIGM-WUR 2023; and propose actions to improve the results of future certifications. The research uses a case study methodology, focusing on Campus I of UFPB. It is a descriptive study with quantitative and qualitative approaches for data collection required by the UIGM-WUR ranking. The G.U.T. Matrix is employed to prioritize actions in the most severe, urgent, and trending indicators, while the SWOT Analysis identifies strengths, weaknesses, opportunities, and threats in the institution's sustainability scenario, aiding in the formulation of improvement proposals and decision-making. As a result of its participation in UIGM-WUR 2023, UFPB ranked 603rd globally and 24th in Brazil among 1183 participating universities, of which 43 are Brazilian. The institution scored 5995 points, representing 59.95% of the total score, a reasonable performance. The waste category had the best performance, achieving 75% of the category's score (860 points), followed by the education and research category with 68.61% (1235 points), and the water category with 65% (650 points). However, the energy and climate change category, with the highest weight, had the lowest performance, scoring 47.62% of the category's points (1000 points), followed by the transport category with 50% (900 points) and the setting and infrastructure category with 57.33% (860 points), reflecting a reasonable performance. Despite the reasonable performance, UFPB has the potential to improve its sustainable practices through environmental programs and initiatives. The emphasis on environmental management and education is crucial for advancing sustainable practices at the university, as it promotes resource use efficiency, reduces negative environmental impacts, and fosters an environmentally conscious university community. Additionally, it equips students with the necessary knowledge to tackle environmental challenges and develop innovative solutions, contributing to the university's leadership in sustainability.